Direct maxillary irrigation therapy in non-operated chronic sinusitis: a prospective randomised controlled trial. Issue 3 (1st March 2022) - Ronen, O; Marshak, T; Uri, N; Gruber, M; Haberfeld, O; Paz, D; Stein, N; Cohen-Kerem, R
Abstract: Objective: This study aimed to compare the effectiveness of pharmacological therapy with and without direct maxillary sinus saline irrigation for the management of chronic rhinosinusitis without polyps. Methods: In this prospective randomised controlled trial, 39 non-operated patients were randomly assigned to be treated with direct maxillary sinus saline irrigation in conjunction with systemic antibiotics and topical sprays ( n = 24) or with pharmacological therapy alone ( n = 15). Endoscopy, Sino-Nasal Outcome Test and Lund–MacKay computed tomography scores were obtained before, six weeks after and one to two years after treatment. Results: Post-treatment Lund–Mackay computed tomography scores were significantly improved in both cohorts, with no inter-cohort difference identified. Post-treatment nasal endoscopy scores were significantly improved in the study group but were similar to those measured in the control group. The Sino-Nasal Outcome Test-20 results showed improvement in both cohorts, with no difference between treatment arms. Conclusion: Maxillary sinus puncture and irrigation with saline, combined with pharmacological treatment improves endoscopic findings in patients with chronic rhinosinusitis without polyps, but has no beneficial effect on symptoms and imaging findings over conservative treatment alone.